The Rule of Law Crisis in the European Union: From Portugal to Poland (and Beyond) - Pereira de Sousa, Inês (Teisė, 2020)
Judicial independence is declared as a primary law obligation to be respected by every national body which may apply or interpret European Union law. Recent legislative reforms of national judicial systems in Poland and other Member States undermine the principles of judicial independence and mutual trust and raise the idea of a rule of law crisis, claiming for an intervention of the European Union.
Keywords: rule of law; European Union; reforms of the judicial system; judicial independence; mutual trust